1958
DOI: 10.1128/jb.76.5.546-548.1958
|View full text |Cite
|
Sign up to set email alerts
|

METABOLIC STUDIES ON BRUCELLA NEOTOMAE (STOENNER AND LACKMAN)

Abstract: Stoenner and Lackman (1957) isolated an organism from the wood rat Neotoma lepida and, on the basis of its behavior on differential dye media, CO2 requirements, and H2S production, regarded it as a new species of Brucella, for which they proposed the name Brucella neotomae. Although recognition of a new species may be justified on the basis of these conventional techniques, it was considered advisable to investigate the oxidative metabolic pattern of the proposed new species on substrates of amino acids, carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1959
1959
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The metabolism of B. neotomae (Stoenner and Lackman, 1957) has been discussed in detail previously by Cameron and Meyer (1958). This organism has metabolic features that show it to be transitional between existing species of Brucella, being similar to B. suis in its carbohydrate utilization, carbon dioxide requirements, and hydrogen sulfide production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The metabolism of B. neotomae (Stoenner and Lackman, 1957) has been discussed in detail previously by Cameron and Meyer (1958). This organism has metabolic features that show it to be transitional between existing species of Brucella, being similar to B. suis in its carbohydrate utilization, carbon dioxide requirements, and hydrogen sulfide production.…”
Section: Discussionmentioning
confidence: 98%
“…which are atypical of the existing species (Stoenner and Lackman, 1957), can also be identified by this method (Cameron and Meyer, 1958). It was therefore considered highly desirable to extend these investigations to include all atypical organisms (types) within each species in order to elucidate, if possible, the metabolic features that constitute an atypical organism.…”
mentioning
confidence: 99%
“…In a previous work, we reported the phylogenetic and genomic characteristics of the B. neotomae strains isolated in these two human cases [ 7 ]. This is relevant, considering that the identification of B. neotomae is not straightforward and to distinguish it from other Brucella species by common bacteriological techniques is difficult [ 9 ]. Several years after the isolation of the etiological agents causing brucellosis in these two patients, the Brucella species were unambiguously identify following MLVA16 and whole genome sequence analysis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They conclude that the effect of thionin and basic fuchsin upon the growth of the organisms within this genus has been the most valuable criterion for species identification, and the fact that the differentiation into three species is biologically sound is reflected in the differing metabolic patterns of the organisms within the species and types, especially when correlated with the bacteriostatic action of the dyes and of H 2 S production. Meyer & Cameron (1958) have found that differences in metabolism are particularly valuable in distinguishing Br. suis from the other two species.…”
Section: B Bacteriologymentioning
confidence: 99%
“…Br. neotomae, isolated from the wood rat by Stoener & Lackman (1957), has been the subject of metabolic studies by Cameron & Meyer (1958). They found by means of manometric techniques that the oxidative metabolic pattern of this proposed new species is not identical with the patterns of any of the three recognized species.…”
Section: B Bacteriologymentioning
confidence: 99%